Implementasi Metode Pembelajaran Outdoor Learning dalam Meningkatkan Hasil Belajar Tematik di MI Al-Miftah Gunung Sindur Bogor - Siti Istiqomah; Fitri Lailasari (Attractive : Innovative Education Journal, 2024)
The purpose of this study was to find out the implementation of learning methods outside the classroom on thematic learning outcomes in class II MI Al-Miftah Gunung Sindur Bogor students.  This study uses a qualitative research approach with descriptive methods. Data collection techniques in the form of observation, interviews and summaries, and data analysis techniques in the form of data reduction, data presentation and drawing conclusions. The results of this study indicate that there is an increase in student learning outcomes using the outdoor learning method. This is evidenced by measuring student learning outcomes in terms of affective, cognitive, and psychomotor. Viewed from the effective aspect, students showed active behavior and increased student interest in learning. From the cognitive aspect, it shows that there is an increase in students' understanding of the material presented. And when viewed from the psychomotor aspect, by implementing outdoor learning it makes students love their environment.